Numerical simulation study on flow field distribution and load characteristics of trans-media aerial underwater vehicle during its water-exit process. (August 2019) - Tan, Tan Junyi; Hu, Junhua; Ge, Yang; Chen, Guoming; Yan, Qimin
Abstract: The oblique water-exit process of a trans-media aerial underwater vehicle is a highly non-linear, unsteady and dramatic process of flow field change. Based on the underwater configuration of a variable trans-media aerial underwater vehicle, the water-exit process of this configuration under typical operating conditions was simulated by CFD fluid simulation software, and the flow field characteristics and load distribution of the vehicle at different stages of the water-exit process were analyzed. The simulation results show that when the vehicle crosses the water-air interface obliquely, the phenomenon of liquid surface deformation and uplift, liquid surface attachment wrapping up the water-exit and wake dragging fracture will occur sequentially, which will lead to sudden change and continuous drastic change of the flow field around the vehicle, forming a backflow zone with different radius and direction on both sides. High-frequency positive and negative alternative oscillation of the body load of the vehicle wrapped by water produces pitching moment.